2020
DOI: 10.1111/are.14566
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary marine microalgae,Tetraselmis suecica, on production, gene expression, protein markers and bacterial count of Pacificwhite shrimp Litopenaeus vannamei

Abstract: The marine flagellated Chlorophyta Tetraselmis suecica is among the most important live food species in marine aquaculture. In the present study, the effects of dietary supplementation of dried marine microalgae, Tetraselmis suecica, on growth performance; feed utilization; chemical composition; gene expression of superoxide dismutase (SOD), glutathione peroxidase (GPx) and insulin-like growth factor 2 (IGF-II) gene of Pacific white shrimp, Litopenaeus vannamei; muscle protein polymorphism; and microbial count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 72 publications
2
59
0
Order By: Relevance
“…Protein is considered the most important ingredients in aquaculture diets. Recently, the microalgae biomass has been extensively utilized in aquatic animal feed, resulting in enhanced growth and survival [9]. Marine rotifer Brachionus plicatilis is considered the main zooplankton utilized as live food for marine larvae in marine hatcheries [81,82].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein is considered the most important ingredients in aquaculture diets. Recently, the microalgae biomass has been extensively utilized in aquatic animal feed, resulting in enhanced growth and survival [9]. Marine rotifer Brachionus plicatilis is considered the main zooplankton utilized as live food for marine larvae in marine hatcheries [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…At present, biodiesel's production cost is from 1.5 to 3-fold more than fossil diesel due to the high cost of raw feedstocks and unavailability of oil crops utilized for human food consumption [2]. Algal biomass are considered an attractive natural source of bioactive materials that can be utilized in several applications such as food industry [3], pharmaceuticals [4], cosmetics [5], biogas and biodiesel [6,7], antimicrobial and antioxidant activities [3,8], aquaculture [9][10][11][12], biofertilizers and bioremediation [13][14][15][16]. Therefore, the screening of native microalgae species is necessary to realize a potent algal database with effective commercial biotechnological applications [3,17].…”
Section: Introductionmentioning
confidence: 99%
“…The employment of seaweed extracts as biostimulants in agricultural practices is very ancient, having been in use since early plant breeding [3]. Based on their nutritional values, algal cells (either microalgae or seaweeds) represent a treasury of sources of dyes, proteins, fats, polyunsaturated fatty acids (PUFA), polysaccharides, minerals, and antioxidants, as well as plenty of biological components [5][6][7][8][9]. In addition, seaweeds have important environmental functions, being one of the most important components of marine ecosystems [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that the constituents, diversity, and communities of marine algae are affected by variations in environmental parameters and nutrient limitation [65][66][67][68][69][70]. During the last few years, the attention on scientific and commercial interest to biotechnological applications of algae as a sustainable source and global commercial for aquaculture [71][72][73][74][75], biofuel [12,76], extracts [77,78], food supplement, pharmaceuticals, and cosmetics were increased [12].…”
Section: Discussionmentioning
confidence: 99%